AN INVESTIGATION INTO THE USE OF COHESIVE DEVICES IN B1 WRITING OF NON-ENGLISH MAJORED JUNIORS AT DONG A UNIVERSITY AND SUGGESTED SOLUTIONS - Tran Thi Phuoc Trang, Tran Thi Phuoc Trang; Nguyen Doan Viet Trinh, Nguyen Doan Viet Trinh (Tạp chí Khoa học Đại học Đông Á, 2025)
This study investigates the use of cohesive devices among third-year non-English major students at Dong A University, specifically in their B1 level writing. A survey involving 100 students was conducted to assess their frequency of use, opinions on five types of cohesive device, and the challenges they face in academic writing. The data collected was analyzed using both quantitative and qualitative methods. A total of 100 midterm essays were reviewed to validate the survey findings. To enhance the reliability and objectivity of the research, feedback from several experts, including B1 instructors, was gathered regarding the curriculum, students' usage of cohesive devices, and their accuracy in application. The results reveal a strong correlation between students' use of cohesive devices and the teaching methods employed by instructors. Despite the frequency of usage, students often encounter difficulties and make errors when utilizing these devices. Based on the findings, the study aims to provide practical recommendations and solutions from educators, along with academic research, to equip third-year non-English major students at Dong A University with effective techniques and skills for using linking words in their B1 level writing. Ultimately, the goal is to enhance the students' writing proficiency by improving their ability to use cohesive devices effectively.